Legal Reasoning Hakim dalam Memutuskan Jumlah Kerugian Materil Sengketa Murabahah di Pengadilan Agama Purwokerto - Umam, Khoerul; Syufaat, Syufaat (Institut Agama Islam Negeri (IAIN) Syekh Nurjati Cirebon, 2023)
Dispute cases in the field of sharia economics are new cases for the Panel of Judges of the Religious Courts since the promulgation of Law Number 3 of 2006, so that with the limitations of formal law and material law relating to cases of sharia economic disputes. So the judges are required to create laws that are progressive as an effort to decide on a case at hand. In this study, the author seeks to explain how a judge applies law to sharia economic cases, especially in case number 6379/Pdt.G/2019/PA.Clp in the Case of Default in the Murabahah Contract at the Cilacap Religious Court.The author in conducting research certainly uses research methods that are in accordance with scientific principles. The type of research used is a type of library research where the data used is primary data, namely the Islamic banking dispute decision Number. Number 6379/Pdt.G/2019/PA.Clp In the Case of Default in the Murabahah Contract at the Cilacap Religious Court with a normative juridical approach. Data collection techniques were carried out by collecting primary and secondary materials, including through interviews with the main source of the Panel of Judges examining the case in order to explore the method of application and discovery of law. Data analysis used descriptive analysis method with deductive qualitative analysis techniques.The results of the study show that the decision of the panel of judges in case number 6379/Pdt.G/2019/PA.Clp produces 2 results, namely the first explains the reasons for the validity of the murabahah agreement in the case and the legal reasoning of the judge in deciding the dispute so as to get a decision that is felt have justice between the two parties and of course have legal certainty.